1991
DOI: 10.1002/art.1790040404
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of self‐efficacy beliefs on adaptation to rheumatoid arthritis

Abstract: This article examines the influence of self‐efficacy beliefs on problem‐solving coping, functional disability, and psychological well‐being for 101 recently diagnosed adult patients with rheumatoid arthritis (RA). Data were drawn from a longitudinal study of psychosocial adaptation to the onset of RA. Self‐efficacy beliefs were associated with less functional disability assessed concurrently and 1 year later. Self‐efficacy beliefs were also associated with greater use of problem‐solving coping 1 year later. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(66 citation statements)
references
References 24 publications
0
62
0
3
Order By: Relevance
“…Pain self-efficacy Pain Self-Efficacy Questionnaire 147 32, 59 SCI self-efficacy Moorong Self-Efficacy Scale 148 31-33, 59…”
Section: Resultsmentioning
confidence: 99%
“…Pain self-efficacy Pain Self-Efficacy Questionnaire 147 32, 59 SCI self-efficacy Moorong Self-Efficacy Scale 148 31-33, 59…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we found that among patients with RA, perceived selfefficacy is an important determinant of compliance with health recommendations and of such health outcomes as pain and disability (14). Other studies have also found associations between perceived self-efficacy and health status among arthritis patients (9,(15)(16)(17)(18). The Arthritis Self-Management Program (ASMP) developed by Kate Lorig and colleagues has been shown to result in increased knowledge, more consistent performance of health practices, and reductions in pain (12,19,20).…”
mentioning
confidence: 89%
“…Expectations for treatment and potential barriers to carrying out the recommendations should be discussed. Psychosocial factors, such as illness beliefs and perceived self-efficacy, have been shown to affect patient outcomes and treatment adherence (10)(11)(12). Education and cognitive-behavioral interventions, such as the Arthritis Self-Management Program, can improve health status and decrease health care utilization (13)(14)(15)(16)(17).…”
Section: Goals Of Ra Managementmentioning
confidence: 99%